Cross-border hospital use: analysis using data linkage across four Australian states - Spilsbury, Katrina; Rosman, D.; Alan, J.; Boyd, James; Ferrante, Anna; Semmens, James (Australasian Medical Publishing, 2015)
Objective: To determine the quality and effectiveness of national data linkage capacity by performing a proof-of-concept project investigating cross-border hospital use and hospital-related deaths. Design, participants and setting: Analysis of person-level linked hospital separation and death registration data of all public and private hospital patients in New South Wales, Queensland and Western Australia and of public hospital patients in South Australia, totalling 7.7 million hospital patients from 1 July 2004 to 30 June 2009. Main outcome measures: Counts and proportions of hospital stays and patient movement patterns. Results: 223 262 patients (3.0%) travelled across a state border to attend hospitals, in particular, far northern and western NSW patients travelling to Queensland and SA hospitals, respectively. A further 48 575 patients (0.6%) moved their place of residence interstate between hospital visits, particularly to and from areas associated with major mining and tourism industries. Over 11 000 cross-border hospital transfers were also identified. Of patients who travelled across a state border to hospital, 2800 (1.3%) died in that hospital. An additional 496 deaths recorded in one jurisdiction occurred within 30 days of hospital separation from another jurisdiction. Conclusions: Access to person-level data linked across jurisdictions identified geographical hot spots of cross-border hospital use and hospitalrelated deaths in Australia. This has implications for planning of health service delivery and for longitudinal follow-up studies, particularly those involving mobile populations.